Performance-Based Budgeting, Preventive Supervision, and Effectiveness of Budget Control - Evada Dewata; Selly Wahyuni; Hadi Jauhari; Anggeraini Oktarida (Faculty of Economics, Universitas Sriwijaya, 2021)
This study aims to determine the effect of performance-based budgeting andpreventive supervision on the effectiveness of budget control. The population in this studywere employees at BPKAD, South Sumatra Province, Indonesia. The sampling techniqueused the purposive sampling technique and obtained as many as 77 respondents. Primarydata were collected in a questionnaire and analyzed using multiple linear regression analysis.Based on the results of the study, it shows that partially, performance-based budgeting andpreventive supervision have a positive and significant effect on the effectiveness of budgetcontrol. The implication of this research is to increase the effectiveness of budget control,namely supervision of the procedures for managing and placing the budget as well asincreasing the competence of government officials in BPKAD, South Sumatra Province.